2012
DOI: 10.7150/ijbs.4499
|View full text |Cite
|
Sign up to set email alerts
|

The Role of α-synuclein and Tau Hyperphosphorylation-Mediated Autophagy and Apoptosis in Lead-induced Learning and Memory Injury

Abstract: Lead (Pb) is a well-known heavy metal in nature. Pb can cause pathophysiological changes in several organ systems including central nervous system. Especially, Pb can affect intelligence development and the ability of learning and memory of children. However, the toxic effects and mechanisms of Pb on learning and memory are still unclear. To clarify the mechanisms of Pb-induced neurotoxicity in hippocampus, and its effect on learning and memory, we chose Sprague-Dawley rats (SD-rats) as experimental subjects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…The present study indicated that in our animal or cell model, the manganese exposure level we set caused tested sites at Ser199, Ser202 sites, Ser396 and Ser404 phosphorylation, with Ser199, Ser396 more sentivity. Other literatures have discovered that other heavy metals, including cadmium, lead caused tau hyperphosphorylation, but showing different phosphorylated sites [33][34][35][36]. Even exposed to Mn, the sites of phosphorylation of tau were not consistent in different models.…”
Section: Abl127 Reduces Mn-induced Tau Hyperphosphorylation By Reversmentioning
confidence: 93%
“…The present study indicated that in our animal or cell model, the manganese exposure level we set caused tested sites at Ser199, Ser202 sites, Ser396 and Ser404 phosphorylation, with Ser199, Ser396 more sentivity. Other literatures have discovered that other heavy metals, including cadmium, lead caused tau hyperphosphorylation, but showing different phosphorylated sites [33][34][35][36]. Even exposed to Mn, the sites of phosphorylation of tau were not consistent in different models.…”
Section: Abl127 Reduces Mn-induced Tau Hyperphosphorylation By Reversmentioning
confidence: 93%
“…Historically, neurodegenerative diseases have been categorized by which of several proteins are produced in unusually high amounts, those relevant to this section of this text being termed the synucleopathies. While the archetypal example is PD, this protein has been correlated closely with AD outcomes (Larson et al ., ; Korff et al ., ) and been described in both TBI (Mondello et al ., ; Acosta et al ., ) and Pb 2+ toxicity (Zhang et al ., ). As well as in the brain, α‐synuclein also has a predilection for forming in the gut wall (Natale et al ., ; Cersosimo et al ., ).…”
Section: New Tnf‐based Insightsmentioning
confidence: 99%
“…More contemporary reviews describe these manifestations in some detail, including negative effects of Pb 2+ on intelligence, learning, memory, executive function, processing speed, language, visuospatial skills and affect (Mason et al, 2014), glutamate release, LTP and synaptic plasticity, increased amyloid precursor protein and increased Aβ (Basha et al, 2005;White et al, 2007) in some detail. Others describe α-synuclein accumulation (Zhang et al, 2012) and increased tau phosphorylation (Li et al, 2010;Zhang et al, 2012;Gassowska et al, 2016). Publications on these topics were contemporary with others linking Pb 2+ exposure with increased TNF production, initially using peripheral cells (Guo et al, 1996;Cheng et al, 2006) but later microglia (Li et al, 2009;Kumawat et al, 2014;Li et al, 2014).…”
Section: Insights From Lead Toxicitymentioning
confidence: 99%
“…COX-2 AGGRAVATES ALZHEIMER'S DISEASE cultured neurons (79,80). In contrast, tau also decreased apoptosis via inhibition of caspase-3 activity in cultured cells (81) and Sprague-Dawley (SD) rats (82). The role of tau in autophagy is controversial (83,84).…”
Section: Signaling Pathways Involved In Mediating the Effects Of Cox-mentioning
confidence: 99%